2010
DOI: 10.1093/jmedent/47.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Correlates of Abundances of Mosquito Species and Stages in Discarded Vehicle Tires

Abstract: Discarded vehicle tires are a common habitat for container mosquito larvae, although the environmental factors that may control their presence or abundance within a tire are largely unknown. We sampled discarded vehicle tires in six sites located within four counties of central Illinois during the spring and summer of 2006 to determine associations between a suite of environmental factors and community composition of container mosquitoes. Our goal was to find patterns of association between environmental facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 46 publications
4
32
1
2
Order By: Relevance
“…Although not all mosquito stages are associated with the same suite of environmental characteristics (e.g., correlates of oviposition rates are not necessarily associated with the number of emergent mosquitoes; Yee et al 2010), our results support the hypothesis that an invasive plant can alter vector behavior in a way that may undermine the effectiveness of disease risk models. Disease control programs rely upon the association between environmental features and vector distributions; a relationship connected by vector behavior (Kalluri et al 2007).…”
Section: Discussionsupporting
confidence: 63%
“…Although not all mosquito stages are associated with the same suite of environmental characteristics (e.g., correlates of oviposition rates are not necessarily associated with the number of emergent mosquitoes; Yee et al 2010), our results support the hypothesis that an invasive plant can alter vector behavior in a way that may undermine the effectiveness of disease risk models. Disease control programs rely upon the association between environmental features and vector distributions; a relationship connected by vector behavior (Kalluri et al 2007).…”
Section: Discussionsupporting
confidence: 63%
“…The potential importance of tires as a source of mosquito vectors was noted during the mid-1940s, when war material was returned to the United States (US) containing tires infested with mosquitoes (Reiter & Sprenger 1987). Since then, tires have been targeted for investigations of mosquitoes worldwide, including North America (Yee et al 2010), Europe (Scholte et al 2010) and Asia (Higa et al 2010). Despite the voluminous literature on these man-made containers and their demonstrated relevance to public health, there are no ecological studies focused on water-filled tires as habitats for mosquitoes in Argentina.…”
mentioning
confidence: 99%
“…albopictus larvae with aspects of the resource environments in field containers. In surveys of tires from six sites among four counties in spring and summer in Illinois, Yee et al (2010) found that abundance of Ae. albopictus larvae was correlated with the presence of detritus (leaf, seed, and fine detritus in spring; seeds in summer).…”
Section: Nutrient Environmentsmentioning
confidence: 99%